2021
DOI: 10.1155/2021/7154250
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and Prevalence of Thyroid Diseases at a Tertiary Referral Hospital in Mogadishu, Somalia: A Retrospective Study of 976 Cases

Abstract: Background. Thyroid disorder is one of the most common noncommunicable diseases worldwide and neglected public health issues in Somalia. The aim of the study thus was to investigate the thyroid disorders in patients attending to the largest tertiary referral hospital in Somalia. Methods. This retrospective study was conducted on patients admitted to the internal department of Somalia Mogadishu-Turkey Education and Research Hospital, Somali, between January 2017 and December 2019. Patients who were tested for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…Hassan-Kadle and colleagues studied 976 patients from Somalia in 2021 to identify the prevalence of thyroid disease in a tertiary hospital. They found that the prevalence rates of primary hypothyroidism and subclinical hypothyroidism were 12.5% and 7.6%, respectively (15). Another study from Somalia regarding the prevalence of thyroid dysfunction among heart failure patients in 2022 which included 250 patients reported that overt hypothyroidism and subclinical hypothyroidism rated in 25.6% and 33.3%, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…Hassan-Kadle and colleagues studied 976 patients from Somalia in 2021 to identify the prevalence of thyroid disease in a tertiary hospital. They found that the prevalence rates of primary hypothyroidism and subclinical hypothyroidism were 12.5% and 7.6%, respectively (15). Another study from Somalia regarding the prevalence of thyroid dysfunction among heart failure patients in 2022 which included 250 patients reported that overt hypothyroidism and subclinical hypothyroidism rated in 25.6% and 33.3%, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid function tests were measured by a Roche e411 Immunoassay Analyzer (Roche Diagnostics Corporation, Indianapolis, IN). 11 The epidemiological and clinical importance of OA and CA in patients with heart failure with mid-range ejection fraction (HFmrEF, defined as LVEF between 40 and 49%) and heart failure with preserved ejection fraction (HFpEF, defined as LVEF between 40 and 49%) (HFpEF, defined as LVEF greater than 50%. 12 , 13 The data was collected using Microsoft excel and was analyzed using Statistical Package for Social Sciences (SPSS) software version 26.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, 90 patients (9.2%) were seropositive (47 have HIV and 43 have HIV + malaria). Out of 90 seropositive patients, 57 (63.3%) have SES, while among seronegative patients the prevalence of SES was 58% (514/886) [ 49 ].…”
Section: Sick Euthyroid Syndromementioning
confidence: 99%
“…Precisely, 17 out of 200 patients (8.5%) were diagnosed with thyroid neoplasia while 38 (19%) had lung cancer [ 33 ]. Papillary thyroid cancer is the most common type of thyroid tumor (82%) in the adult and the pediatric population both in PLWH and in the general population, followed by follicular (7%) carcinoma, medullary thyroid tumor (3%) and anaplastic tumor (1%) [ 49 , 88 , 89 , 91 ]. In the study of Properzi et al, out of 11 PLWH with thyroid cancer, medullary thyroid cancer occurs in 2 patients (18.18%) [ 12 ].…”
Section: Thyroid Neoplasiamentioning
confidence: 99%